Proceedings of the International Conference on Strategic Issues of Economics, Business And, Education (ICoSIEBE 2020) 2021
DOI: 10.2991/aebmr.k.210220.039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Capital Intensity and Inventory Intensity on Tax Avoidance at Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange (IDX)

Abstract: This study aims to determine whether the significant influence of the Capital Intensity and Inventory Intensity Against Tax Avoidance in the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the period 2014 -2018. The population in this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2014 -2018 as many as 18 companies. The research sample in this study as many as 10 companies by purposive sampling technique. The result of the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 2 publications
(4 reference statements)
1
5
0
7
Order By: Relevance
“…The assets owned by the company are used for business purposes, including maximum operational and investment support so that the company is able to pay its taxes and does not need to do tax avoidance. The finding is consistent with previous studies (Ristanti, 2022;Nugrahadi & Rinaldi, 2021;Sulistiyanti & Nugraha, 2019) that capital intensity has no effect on tax avoidance. However, the results of this study are contrary to research by Ratu & Meiriasari (2021).…”
Section: The Effect Of Capital Intensity On Tax Avoidancesupporting
confidence: 93%
See 1 more Smart Citation
“…The assets owned by the company are used for business purposes, including maximum operational and investment support so that the company is able to pay its taxes and does not need to do tax avoidance. The finding is consistent with previous studies (Ristanti, 2022;Nugrahadi & Rinaldi, 2021;Sulistiyanti & Nugraha, 2019) that capital intensity has no effect on tax avoidance. However, the results of this study are contrary to research by Ratu & Meiriasari (2021).…”
Section: The Effect Of Capital Intensity On Tax Avoidancesupporting
confidence: 93%
“…(Sugeng et al, 2020). Ratu and Meiriasari (2021) and Nugrahadi and Rinaldi (2021) reported that capital intensity and avoidance of taxes is significantly correlated. Since fixed assets cause depreciation expense, depreciation expense on ownership of fixed assets will reduce the tax payments the company would pay.…”
Section: Tax Avoidance and Capital Intensitymentioning
confidence: 99%
“…Sebelumnya telah dilakukan beberapa penelitian dan menghasilkan kesimpulan yang beragam. Menurut (Nugrahadi & Rinaldi, 2021), (Maulida & Karak, 2021), (Nugraha, 2020), (Kasim & Saad, 2019) menjelaskan bahwa perputaran persediaan, capital intensity, leverage, dan ukuran perusahaan berdampak secara parsial terhadap tax avoidance. Sedangkan (Misral et al, 2020), (S. M. , (Sari, 2021) menyatakan variabel-variabel tersebut memiliki dampak secara signifikan pada tax avoidance.…”
Section: Pendahuluanunclassified
“…Intensitas persediaan adalah perusahaan berinvestasi dalam bentuk persediaan ke dalam perusahaan (Bowo 2018;Fahrani et al, 2018;Nugrahadi and Rinaldi 2021;Puspita et al, 2020;Sugeng et al, 2020;Syamsuddin 2019). Menurut pendapat Ann and Manurung (2019), Dwiyanti and Jati (2019) dan Pratama and Suryarini (2020) intensitas persediaan menunjukkan seberapa banyak persediaan yang dimiliki perusahaan, tetapi semua itu tergantung pada cara pengelolaan manajemen persediaan dan aset lain yang menghasilkan laba.…”
Section: Landasan Teori Dan Pengembangan Hipotesis Intensitas Persedi...unclassified
“…Perusahaan dengan tingkat intensitas persediaan yang tinggi, maka semakin rendah ETR yang dimilikinya dan akan lebih agresif terhadap tingkat beban pajak yang diterima perusahaan (Andhari and Sukartha 2017;Avrinia Wulansari et al, 2020;Pratama and Suryarini 2020;Puspita et al, 2020;Ramadhani and Azmi 2019;Sonia and Suparmun 2019;Yuliana and Wahyudi 2018). Hal tersebut telah didukung oleh penelitian sebelumnya yang telah dilakukan oleh Ann and Manurung (2019), Puspita et al, (2020), Yuliana and Wahyudi (2018), Fahrani et al, (2018), Bowo (2018), Maulana (2020), Dwiyanti and Jati (2019), Nugrahadi and Rinaldi (2021) dan Syamsuddin (2019) yang menunjukkan bahwa terdapat pengaruh positif antara hubungan intensitas persediaan terhadap agresivitas pajak. Berdasarkan uraian di atas dapat dirumuskan menjadi hipotesis penelitian sebagai berikut: H1: Intensitas persediaan berpengaruh positif terhadap agresivitas pajak.…”
Section: Landasan Teori Dan Pengembangan Hipotesis Intensitas Persedi...unclassified